Tax Criminality During the Pandemic – Risks and Predictions - Božić, Vanda; Dimić, Suzana; Đukić, Mirjana (Kriminalističke teme, 2022)
The year-long pending Covid-19 pandemic has primarily been imposing significant consequences to health. Apart from these, there are emerging negative effects in all society segments, particularly those related to criminal activities. Deviant persons have always exploited fear and social insecurity during war devastation and pandemics as an ideal ground for their criminal activities, therefore we can start from the assumption that current situation bears a high degree of risk of increase in various illegal behaviours. In the study the authors have elaborated on the risks imposed by the pandemic on increase of certain types of tax crimes. Diminished capacity of financial institutions to enforce control over financial transactions makes it easier for taxpayers to actualize the intended tax fraud, leading to acquisition of illegal revenue and even, in some cases, to the criminal act of money laundering. As tax evasion may result from identity theft of taxpayers, hacking attacks are expected to intensify, therefore we need to reinforce the activities of tax administration officers. It should be emphasized that transition to service concept of tax institution operation, as well as transfer of a considerable share of activities onto the individual taxpayer, have lead to a certain inertness of tax institutions. The study offers predictions and proposals of short-term de lege ferenda, based on the current epidemiological situation.